Offender Recidivism: A Quantitative Study of Motivational Risk Factors and Counseling - Dadashazar, Nazak (2017)
The prison system releases over 590,000 inmates annually, adding to the current 5 million ex-offenders on supervised release. The purpose of this study was to explore the problem of increasing recidivism by identifying ex-offenders' dynamic risk and criminogenic need factors using the Level of Service Inventory-Revised (LSI-R), coupled with or without mental health services during reentry in relation to recidivism. This quantitative, nonexperimental, cross-sectional study included data collected from a sample of 128 male recidivist and nonrecidivist federal ex-offenders currently on supervised release, who were recruited during probation office meetings within the South Texas region. Regression analysis yielded statistical significance for all 3 of the study's research questions (RQ). RQ1 was to determine whether a difference existed between the LSI-R scores of recidivist and nonrecidivist ex-offenders. RQ2 was to determine if there was a difference in the LSI-R scores of ex-offenders who have or have not attended mental health counseling during reentry. RQ3 was to determine whether there was a relationship between ex-offenders who have undergone counseling or not during reentry and recidivism. The analysis revealed a correlation between ex-offender's risk factors, counseling received, and recidivism. A recommendation from this study is to increase research and specialized training in forensic counseling in the counseling field, currently not required by the Council for Accreditation of Counseling and Related Educational Programs (CACREP). Furthermore, the findings of this study could contribute to positive social change for the prison officials, reentry agencies, and forensic mental health professionals in identifying higher-risk factors to help combat recidivism